A Comparative Study Between Pemetrexed and Taxanes as First Line Treatment of Metastatic Lung Adenocarcinoma - Qahtan Al-Salihi, Sarmad; Sabieh Al Zubaidi, Azhar (Diyala Journal of Medicine, 2024)
Background: Adenocarcinoma of the lung is the most common type of lung cancer. Platinum agents in combination with other chemotherapy are currently the cornerstone for chemotherapy of advanced cases with metastasis. Objective: To compare the response rate of pemetrexed doublets versus taxanes doublets in patients with metastatic lung adenocarcinoma. Patients and Methods: This a prospective study that included 60 patients with pulmonary adenocarcinoma. Those patients received a platinum based doublet chemotherapy with additional treatment protocol; combined with either pemetrexed or taxanes (paclitaxel or docetaxel) with 30 patients in each arm. Tumor size, response rate and side effects of chemotherapy were evaluated in both arms. Results: The median reduction in tumor size in pemetrexed and taxan arms were 4.72 cm2 and 6.53 cm2 respectively. Nausea, fatigue, constipation and anorexia were more common in pemetrexed arm, while leukopenia, arthralgia and peripheral neuropathy were more common in taxan arm. Conclusion: Serious side effects such as leukopenia, and peripheral neuropathy were more common in taxan than pemetrexed arm. Pemetrexed is preferable to use as a fist line treatment for patients with metastatic adenocarcinoma of the lung.